Perspektif Akuntansi dalam Ekonomi Islam - Syaiful Bahri; Daryo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In several ways, the sharia accounting system is different from conventional accounting. However, there are axiomatic technical similarities between the two. By using descriptive qualitative methods, this research aims to provide the author with an understanding of accounting theory and practice in Islamic economics. The research results show that the perspective of accounting science in Islamic economic practice focuses on the use of an accounting system that is in accordance with sharia principles, which prioritizes truth, accuracy and fairness. Surah Al-Baqarah verse 282 emphasizes clear and accurate transaction recording, the use of honest writers, financial accountability, zakat, and transparency and fairness in accounting. The results of this research conclude that there are many ways to see the economic implications of Islam today. First, Islamic economics must adapt to technological changes because they have influenced the way people think and act. Second, the history of Islamic economics has changed in the modern era, and third, Islamic economics is now real and relevant with the development of digital technology. Fourth, the concept of Islamic economics is based on the Koran and Sunnah. Compared to Conventional Accounting: Sharia accounting systems differ from conventional accounting in several key aspects. However, there are axiomatic technical similarities between the two.